Metal concentrations in Silver pomfret Pampus argenteus (Euphrasen, 1788) and its risk assessment in Malaysia - SUZYELAWATI MOHD SHUKRI; AHMAD DWI SETYAWAN; DARLINA MD NAIM (Nusantara Bioscience, 2024)
Abstract. Shukri SM, Setyawan AD, MD Naim D. 2024. Metal concentrations in Silver pomfret Pampus argenteus (Euphrasen, 1788) and its risk assessment in Malaysia. Nusantara Bioscience 16: 13-22. Fish consumption is one of the most important sources of protein in Malaysia. Nevertheless, anthropogenic sources release contaminants, such as metals, which have the potential to accumulate within marine organisms via the food chain. Hence, ingesting fish polluted with metals can be potentially hazardous to human health. This study aimed to ascertain the levels of metal concentrations in the edible tissues of Pampus argenteus (Euphrasen, 1788) inhabiting Malaysian waters to evaluate potential health hazards associated with their use. This study examines the levels of three metals, specifically Cd, Ni, and Pb, in P. argenteus. The samples underwent microwave digestion in a closed vessel to extract metals, which were subsequently analyzed using ICP-OES. The study revealed that the quantities of metals in P. argenteus were primarily Pb, with Ni and Cd following suit. These values ranged from 0.651 mg/kg to 0.001 mg/kg when measured on a dry weight basis. Notably, the samples collected from the Straits of Malacca exhibit a greater concentration of metals than those obtained from the South China Sea region. The tolerable daily intake of P. argenteus from all populations in this study was below the FAO/WHO oral reference dose. The risk assessment results showed that all populations' target hazard quotient was below 1.0. The results indicate that exposure to the metals studied poses a low non-carcinogenic risk and is considered safe for human consumption. This research offers baseline data for evaluating food safety and developing risk management recommendations concerning P. argenteus.